Carceral churn: A sensorial ethnography of the bail and remand court - Russell, Emma K. (Punishment & society, 2022)
This article discusses findings from an ethnographic study of a bail and remand court in Victoria, Australia. Through a focus on the sensory dimensions of forced movements within and through the bail court, the article contributes to the burgeoning sub-field of sensory criminology and develops the concept of ‘carceral churn’. The article argues that the bail court’s churn reproduces criminal and carceral subjects and is implicated in a project of carceral buildup. The churn of the bail court involves forms of mobility and exchange via the inter- and intra-carceral spaces that variously dull, distort, deprive or assault the senses with oppressive effects. This includes both ‘new’ and ‘old’ penal technologies such as holding cells, the custody dock, AV links and court-prison transport. The analysis of sensory violence challenges the notion that court ‘efficiency’ can improve justice experiences and outcomes and instead calls for increased attention to the harms and lethality that flow from carceral churn left un-checked.